Health Seeking Behaviour in Omambala Area of Anambra State: The Predictive Role of Health Consciousness (Practicum Psychologia, 2026)
The study determined the predictive role of health consciousness on health seeking behaviour in Omambala Area of Anambra State. A total number of 131 patients drawn from Omambala Area (Umueri General Hospital and Immaculate Heart Multispecialty Hospital, Aguleri) Anambra East Local Government Area, were used in the study. The study utilized non-probability (purposive sampling technique) in selecting the hospitals and participants. The participants’ age ranged from 45 to 79 years with mean age of 64.08 and standard deviation of 9.66. Gender data revealed that 33(25.2%) were males and 98(74.8%) were females. New Health Consciousness Scale and Health Seeking Behaviour scale were employed for the study. The study adopted a correlational design and Multiple Linear Regression statistics. Results showed that health consciousness (self-consciousness, health value, health information, physical health orientation, mental health orientation, health motivation, health knowledge, and health responsibility) and perceived knowledge of cardiovascular disease risk (Perceived risk to heart attack/stroke, perceived benefit and intention to change and perceived eating intention) accounted for 76.2% of the health seeking behaviour, with R2 = .762, adjusted R2=.740, (F11, 119) = 34.70, p